Tārīkh nashʾat al-naḥw wa-al-dirāsah ʿan taṭawwurih - Habibi, Nicolas; Aan, Milki; Harianto, Neldi; Malik, Khairil (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This research proved that Abu Al-Aswad Al-Du’ali is the first to think about putting the science of grammar in pushing the danger of melody from the Qur’anic text and language. After Abu al-Aswad, his disciples came and continued his way. Then their students came and followed the approach of their teacher, until grammar matured at the hands of Al-Khalil bin Ahmad, the author of the first grammar book that reached us. Thus, Al-Khalil was able to present Arabic as a structural model for describing Arabic phonetically, morphologically, grammatically and lexically. This science was spread until the twentieth century. There have been many attempts to facilitate at all levels, and I mention some examples of representation, but not limited to, as follows: Revival of grammar: by Ibrahim Mustafa; Critical Studies in Arabic Grammar: by Abdul Rahman Ayoub; Towards Facilitation: by Ahmed Abdul Sattar Al-Jawari; In Arabic grammar, criticism and guidance: by Mahdi Makhzoumi. The method of this research is the method of descriptive analytical to describe the emergence of grammar and to support this method the writer used the method of synchronous analysis and temporal analysis.